2020
DOI: 10.13057/bonorowo/w100102
|View full text |Cite
|
Sign up to set email alerts
|

Structure and biomass accumulation of natural mangrove forest at Gazi Bay, Kenya

Abstract: Abstract. Githaiga MN, Kotut K, Kariuki F, Kairo JG. 2019. Structure and biomass accumulation of natural mangrove forest at Gazi Bay, Kenya. Bonorowo Wetlands 9: 18-32. The goal of this study was to determine the forest structure and estimate biomass accumulation above and below ground in the mangrove forest of Gazi Bay. The western, middle, and eastern forest blocks of the Gazi Bay mangrove forest were investigated for forest structure, whereas the western forest block was determined for biomass accumulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 61 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…This in agreement with Yang et al (2014) who reported that vegetation type affects soil carbon storage. The variation in mangrove land cover was also observed by Daud et al (2022) in Zanzibar, Githaiga (2013) in Kenya, Dung et al (2016) in Can Gio (Vietnam) mangroves forest, which is consistent with global data (Jardine & Siikamaki, 2014). The differences in SOC stocks among forests can be explained by differences in density and aerial root type (Xiong et al, 2018).…”
Section: Soil Carbon In Function Of Locations and Mangrove Forests Typessupporting
confidence: 87%
“…This in agreement with Yang et al (2014) who reported that vegetation type affects soil carbon storage. The variation in mangrove land cover was also observed by Daud et al (2022) in Zanzibar, Githaiga (2013) in Kenya, Dung et al (2016) in Can Gio (Vietnam) mangroves forest, which is consistent with global data (Jardine & Siikamaki, 2014). The differences in SOC stocks among forests can be explained by differences in density and aerial root type (Xiong et al, 2018).…”
Section: Soil Carbon In Function Of Locations and Mangrove Forests Typessupporting
confidence: 87%
“…The seaward side is occupied by Sonneratia alba. This 4 is followed by Rhizophora mucronata -Bruguiera gymnorrhiza in the mid-zone and the Ceriops tagal, Avicennia marina and Lumnitzera racemose on the landward side [49].…”
Section: Mangroves In Gazi Baymentioning
confidence: 97%
“…Historically, mangroves in Gazi bay have been exploited for wood and non-wood resources [49,50]. In the 1970s and 1980s industrial exploitation of mangrove wood for energy in Gazi left large contiguous blank areas, some of which have failed to regenerate naturally [41,51].…”
Section: History Of Mangrove Exploitation and Management Intervention...mentioning
confidence: 99%
See 1 more Smart Citation
“…When 'blue carbon' appeared on the climate policy agenda in 2009, the 615 hectares of mangrove forest at Gazi Bay were arguably already the most thoroughly researched mangroves in Africa and among the most well researched on Earth (Huxham, 2011). This is because, from the early 1990s, in line with Kenya's aims to enhance the national forestry sector and coinciding with early experiments in forestry-based voluntary emissions offsetting by US-based firms, the KMFRI initiated trial mangrove plantations, and Gazi Bay was selected as a pilot area (Bellassen and Leguet, 2007;Kairo, 1995b;Watt, 2021). Members of mangrove-adjacent communities were encouraged to create plantations using native varieties (Rhizphora mucronata, Ceriops tagal, Bruguiera gymnorrhiza, Avicennia marina and Sonneratia alba) in areas that had been severely disturbed or deforested in the 1970s (Ingwall, 2005).…”
Section: Making the 'Blue Forest'mentioning
confidence: 99%